INDUSTRY-REGIONAL APPROACH TO FORMING AN EFFECTIVE FOOD POLICY IN THE AGRICULTURAL SECTOR - BORBOLIUK, Yevhen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the conceptual principles of implementing a sector-regional approach to forming an effective food policy in the agricultural sector of Ukraine. The need for comprehensive consideration of sectoral features of agricultural production and regional specifics of rural development is substantiated to achieve food security, sustainability of agri-food systems, and socio economic growth. It is emphasized that modern challenges - in particular geopolitical instability, climate change, disruption of logistics chains, growing needs for safe and affordable food - require a transition from a unified food policy to a differentiated approach that takes into account agricultural specialization, the level of infrastructure, natural and climatic conditions, the state of land resources and socio-demographic factors of individual regions. A theoretical and methodological model of integrating sectoral and regional indicators for making management decisions in the field of food policy is proposed. The strengths and weaknesses of the agri-food potential of various regions of Ukraine are analyzed, and strategic directions for the development of highly efficient, environmentally sustainable and socially oriented agrarian regions are identified. The importance of involving local stakeholders, including communities, business and the scientific community, in the development of adaptive food management mechanisms is emphasized. The conclusions are drawn that the sectoral-regional approach allows adapting food policy to the specifics of agricultural production in different regions, increasing its efficiency. In addition, the differentiation of agricultural strategies by sectors and regions will contribute to the rational use of resources, stimulate the development of local competitive advantages. The implementation of such an approach requires a systematic analysis, the availability of reliable statistics and the active participation of regional stakeholders. State support instruments should be flexible and targeted, taking into account both the sectoral structure and the socio-economic state of the territories. The implementation of the sectoral-regional approach will contribute to strengthening the food security of Ukraine, the development of the agricultural market and the reduction of interregional disparities.